A successful treatment of ganglionated plexi ablation for vagally mediated nocturnal atrioventricular block. Issue 3 (September 2022) - Kobayashi, Masanori; Ichikawa, Tomohide; Wakabayashi, Yasushi; Koyama, Takashi; Abe, Hidetoshi; Itoh, Mitsuaki; Yamashiro, Kohei
Abstract: Patients suffering from sleep-related bradyarrhythmias are often underdiagnosed, due to the presence of asymptomatic cases. Although the consequence of increased nocturnal parasympathetic nerve activities and decreased sympathetic nerve activity during sleep are associated with nocturnal bradyarrhythmias, the detailed mechanisms are still unknown. It is well known that ganglionated plexi (GP) ablation is an effective therapeutic approach to modify autonomic nerve functions. Here, we report a case of successful treatment for the vagally mediated long ventricular pauses during sleep using autonomic modulation through GP ablation. Learning objective: Sleep-related bradyarrhythmias unrelated to sleep apnea or hypopnea are rare sleep disorders. Treatment of this disorder has not been established. High-frequency stimulation guided ganglionated plexi ablation could be an effective therapeutic approach to achieve long-term vagal attenuation to prevent vagally induced nocturnal bradyarrhythmias.